2006
DOI: 10.1016/j.neuron.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Control of Corticostriatal Long-Term Synaptic Depression in Medium Spiny Neurons Is Mediated by Cholinergic Interneurons

Abstract: Long-term depression (LTD) of the synapse formed between cortical pyramidal neurons and striatal medium spiny neurons is central to many theories of motor plasticity and associative learning. The induction of LTD at this synapse is thought to depend upon D(2) dopamine receptors localized in the postsynaptic membrane. If this were true, LTD should be inducible in neurons from only one of the two projection systems of the striatum. Using transgenic mice in which neurons that contribute to these two systems are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
440
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(470 citation statements)
references
References 49 publications
22
440
4
Order By: Relevance
“…Using intracellular loading with the patch pipette, we also showed that inhibition of translation in the postsynaptic cell did not block striatal LTD, although the same treatment blocked a different form of LTD in the hippocampus. The latter experiment demonstrates that cycloheximide is easily loaded into the postsynaptic neuron, and we know from past studies that larger molecules, such as Alexa Fluor 594, can be loaded easily into medium spiny neurons via the patch pipette (Wang et al, 2006). Thus, the lack of effect of postsynaptic cycloheximide loading on striatal LTD is not likely attributable to the inability of the drug to reach the relevant sites in the postsynaptic neuron.…”
Section: Discussionmentioning
confidence: 81%
“…Using intracellular loading with the patch pipette, we also showed that inhibition of translation in the postsynaptic cell did not block striatal LTD, although the same treatment blocked a different form of LTD in the hippocampus. The latter experiment demonstrates that cycloheximide is easily loaded into the postsynaptic neuron, and we know from past studies that larger molecules, such as Alexa Fluor 594, can be loaded easily into medium spiny neurons via the patch pipette (Wang et al, 2006). Thus, the lack of effect of postsynaptic cycloheximide loading on striatal LTD is not likely attributable to the inability of the drug to reach the relevant sites in the postsynaptic neuron.…”
Section: Discussionmentioning
confidence: 81%
“…It is generally agreed that this LTD depends on activation of both D1-and D2-class receptors [9]. However, opinions differ with respect to the cell types that express this plasticity (striatopallidal vs. striatonigral), the sites of dopaminergic action (spines on postsynaptic MSN vs. presynaptic cholinergic interneurons), and the signaling mechanisms [66][67]. NMDAR-dependent striatal LTP can also be induced by high-frequency stimulation of corticostriatal glutamatergic inputs.…”
Section: Functional Evidencementioning
confidence: 99%
“…Dopaminergic inputs to the ventral striatum arise from the ventral tegmentum (VTA) and substantia nigra (SN), which themselves are recipients of cholinergic projections from PM neurons. Activation of a variety of pre-and postsynaptic dopamine receptors strongly regulates the release of ACh and the excitability of striatal cholinergic interneurons (Maurice et al, 2004;Wang et al, 2006). In addition, local circuits of opiate peptide and GABAergic neurons influence the net levels of striatal cholinergic tone.…”
Section: A Cholinergic Pathways Within the Ventral Striatummentioning
confidence: 99%
“…Nevertheless, recent progress in dissecting the interaction of cholinergic circuits with dopaminergic and glutamatergic inputs to the striatum inspires considerable hope that we may be approaching a bona fide understanding of how ACh works at least in one region that is known to effect in schizophrenia and that is particularly high in ACh tone (see below and Cragg, 2006;Calabresi et al, 2000;Wilson, 2006;Wonnacott, 2005 for reviews; Wang et al, 2006).…”
Section: A Cholinergic Pathways Within the Ventral Striatummentioning
confidence: 99%